The association between political environment and COVID-19 mortality in selected Colorado counties - DeBie, Kelly, author; Neophytou, Andreas, advisor; Peel, Jennifer, advisor; Gutilla, Molly, committee member; Rojas-Rueda, David, committee member (Colorado State University. Libraries, 2023)
The SARS-CoV-2 virus spread worldwide triggering a global Coronavirus (COVID-19) pandemic. COVID-19 remains a public health threat today and may continue to do so into the future dependent on the emergence of variants and our ability to mitigate harm through vaccines and other public health measures. The COVID-19 pandemic struck the United States during a time of great political tension and divide under the administration of President Donald Trump. State-level variation in mitigation measures may have been influenced by political views. COVID-19 mortality rates also varied by county. This paper seeks to investigate whether the county-level political environment was associated with differences in COVID-19 mortality in the state of Colorado. We examined the association between political environment and county-level age-adjusted COVID-19 mortality rates during 2020 and 2021. Political environment is measured using data from the 2016 and 2020 Presidential election vote distribution by county, obtained from the Colorado Secretary of State. Outcome data was obtained from the Colorado Department of Public Health and Environment (CDPHE), having already been age-adjusted using direct standardization based on the 2010 Census. Any counties with 3 of fewer deaths in a calendar year were excluded, leaving a total of 48 counties in 2020 and 56 in 2021. Rate ratios and 95% confidence intervals were estimated using Quasi-Poisson regression models, separately for 2020 and 2021 mortality data. The models were adjusted for population density, the percentage of county residents without health insurance, and the demographics percentile from the Colorado EnviroScreen Environmental Justice Tool. Models were further evaluated for the presence of effect modification by population density. There are a total of 64 counties in the state of Colorado. In the 2016 election, 42 counties voted for Donald Trump. In the 2020 election, that dropped to 40 counties. Age-adjusted mortality rates ranged from 14.3-458.0 per 100,000 over the two years of data. For 2021 mortality data, the estimated mean adjusted mortality rate was 78% higher among counties where aggregated individual votes were highest in percentage for Donald Trump in 2016 as compared to counties with highest vote percentage for Hilary Clinton. (RR = 1.78; 95% CI: 1.26-2.59). For 2020, the estimated mean adjusted mortality rate was found to be 24% higher among counties voting in highest percentage for Donald Trump in 2016 as compared to counties voting in highest percentage for Hilary Clinton, though this association was not statistically significant. (RR=1.24; 95% CI: 0.81-1.94). Similar results were observed for the 2020 election data (comparing county-level voting results for Trump vs. Biden). We did not observe evidence that the association was modified by population density. This study observed an association between county-level political environment and age-adjusted COVID-19 mortality rates, specifically finding an association that became statistically significant during the pandemic. These results build on a growing body of evidence studying the links between politics and COVID-19 outcomes. Strengths of this study include the use of publicly available datasets, state-wide analysis, multiple model options with similar results indicating robustness, and utilization of a novel environmental justice metric to adjust for multiple confounders simultaneously. As this was an ecological study, inference cannot be extended to individuals. Future research may want to further explore both the individual and community political exposures that may influence mortality. It may also be suggested to investigate election data as a continuous rather than binary variable to tease out the relationship in more detail. Studies such as this may be useful as the COVID-19 pandemic is still ongoing, and in preparation for any future pandemics.
Keywords: epidemiology; politics; COVID-19; public; health